The Dynamic Response of the Budget Balance to Tax, Spending and Output Shocks: Does Model Specification Matter? - Göran Hjelm (Lund University, School of Economics and Management, Department of Economics, 2001)
This paper estimates how the US budget responds to shocks in taxes, spending and output. In particular, we consider the dynamic adjustment of the two budget components (taxes and spending) to such shocks. The recently developed Generalized Impulse Response Function, which takes the historical distribution of the residuals into account, is applied. We select the 'correct' specification, estimate two VAR and two VEC models and compare the results. Our chosen specification suggests that tax, spending and output shocks generate deficits in the long run while the tax and output shocks generate a surplus in the short run. Moreover, model specification matters indeed.
Keywords: C32; C52; E62; 330; Generalized impulse response function; Model specification; VAR; Budget deficit; Fiscal variables